Exposure hazards of oxidative stress in environmental pollutants and application of plant antioxidants. Issue 5 (May 2021) - Li, Changlei; Chen, Xiaoqing; Yi, Hui Ling; Ma, Baomiao
Abstract: Environmental chemical pollutants are diverse and have complex and varied exposure forms. The release of these pollutants into the environment will cause oxidative stress reaction, which is caused by excessive and uncontrolled reactive oxygen species damage to proteins, lipids and DNA. To protect the health of humans and other species, the crack problem of environmental protection, through continuous exploration, found in acid medium, rhodamine B can produce characteristic fluorescence, Feton system to produce hydroxyl radicals can rapid oxidation of rhodamine B fluorescence quenching, and many natural antioxidants can partially remove hydroxyl radicals in solution, reduce the degree of fluorescence quenching. Based on this principle, a new method for the determination of the antioxidant activity of oligosaccharide proanthocyanidins was established, which provides a new way to solve the problem of environmental pollution.